Writing the Australian Beach
XVI, 243 p. 14 illus., 13 illus. in color.
Keywords: Writing the Australian Beach is the first in fifteen years to explore creative and cultural representations of this iconic landscape, and how writers and scholars have attempted to understand and depict it. Although the content chiefly focuses on Australia, the beach as both a location and idea resonates deeply with readers around the world. This edited collection includes three sections. Forms of Beach Writing examines the history of beach writing in Australia and in a number of forms: screenwriting, social media writing, and food writing. In turn, Multiplicities of Australian Beach Writing examines how forms of writing—poetry, travel writing, horror film, and memoir—engage with some specific beaches in Australia. And, finally, Reading the Beach as a Text considers how the beach itself functions in cultural narratives: how we walk the beach; the revealing story of beach soccer; and the design and use of ocean baths. Givenits scope, the collection offers a unique resource for scholars of Australian culture and creative writing, and for all those interested in Australian beaches. .